2019
DOI: 10.1103/physrevd.100.044031
|View full text |Cite
|
Sign up to set email alerts
|

Particle motions and gravitational lensing in de Rham-Gabadadze-Tolley massive gravity theory

Abstract: We investigate gravitational lensing and particle motions around non-asymptotically flat black hole spacetime in non-linear, ghost-free massive gravity theory, called de Rham-Gabadadze-Tolley (dRGT) massive gravity. Deflection angle formulae are derived in terms of perihelion parameter. The deflection angle can be positive, zero or even negative with various perihelion distance. The negative angle reveals repulsive behaviour of gravity from a linear term γ in the dRGT black hole solution. We also find an analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
(64 reference statements)
0
14
0
1
Order By: Relevance
“…Many studies have been performed to investigate the deviation e.g. quasinormal modes [36], greybody factor [37] and gravitational lensing [38].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed to investigate the deviation e.g. quasinormal modes [36], greybody factor [37] and gravitational lensing [38].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that gravitational lensing and particle motions around non-asymptotically flat black hole spacetime in dRGT massive gravity have been addressed in Ref. [63].…”
Section: Discussionmentioning
confidence: 99%
“…4) It acts, through an entanglement bond, between the real protons orbiting in proton star, on the one hand, and the electrons that most likely revolve in the innermost band of the space surrounding the proton star, in which case it is attractive-repulsive at same time. After all in some recent researches, in particular see references [9] and [10], it has been shown that the possible trajectories of photons and of particles inside and around the black hole are compatible with a repulsive behavior of gravity. In the reference [11], then, a repulsive gravity was shown within the black hole even in the Stueckelberg Quantum formalism;…”
Section:  513 -The Reason Of Non-decreasing Velocity Of Stars and Of Electronsmentioning
confidence: 99%